Effect of Mycoplasma agalactiae mastitis on milk production and composition in Valle dell Belice dairy sheep. Issue 1 (2nd January 2019) - Tolone, Marco; Sutera, Anna Maria; Borrello, Silvio; Tumino, Serena; Scatassa, Maria Luisa; Portolano, Baldassare; Puleio, Roberto; Nicholas, Robin AJ; Loria, Guido Ruggero
Abstract: Contagious agalactia (CA), a disease caused by Mycoplasma agalactiae and other pathogenic mycoplasmas, is a well-known multietiological syndrome affecting dairy breeds of sheep and goats in the Mediterranean basin. The aim of this work was to study the effect on milk production and composition of mastitis caused by M. agalactiae in Valle del Belice dairy sheep. All ewes were manually milked twice daily and the milk from both daily milking was analysed for milk composition and somatic cell counts. Moreover the morning milk samples were collected aseptically from each animal for bacteriological analyses. A mixed linear model was utilised to consider milk production and composition between animals infected by CA and healthy animals. After bacteriological investigation using both cultural and molecular methods, 37 ewes were found to be infected by M. agalactiae while 50 uninfected ewes were randomly selected from the same herds to compare milk production and composition between infected and healthy animals. Statistical analyses showed that the infection with M. agalactiae had a significant effect on yield and some milk components. In particular, infected ewes showed lower milk production with lower lactose content and higher somatic cell counts. The implementation of disease control programmes based on rapid laboratory diagnosis and modern control methods is desirable for Mediterranean endemic areas. Highlights: Contagious agalactia is caused by M. agalactiae and affects small ruminant dairy farms in the Mediterranean basin. Contagious agalactia is endemic in many countries and has a severe health and economic impact. Effect on milk production and composition of mastitis caused by M. agalactiae.